Study on the evolution of the financial support granted to the agricultural sector in the period 2008-2019 - Diana Maria Necula; Bădan Daniela Nicoleta (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The Common Agricultural Policy is the basis for ensuring food security, the sustainable use of natural resources and the balanced development of rural areas in the Member States of the European Union. The three paths of the CAP through which these objectives are achieved are: direct payments, market measures and rural development. In the last ten years, Romania's agricultural development has been achieved with the help of European subsidies established on the basis of the European Common Agricultural Policy. At national level, over 70% of the total funds allocated to the agricultural sector are managed by the Agency for Payments and Intervention for Agriculture, which registered over 1 million beneficiaries, with a funding of over 15 billion euros. This study aims to analyze the evolution of financial support to the agricultural sector through direct payment schemes in Pillar I, in the period 2008-2019, using statistical methods of analysis, thus creating a broader view of the situation of these support schemes.
Keywords: Q14; Q18; 330; financial support; pillar I; direct payments